Recent Advances on the Carboxylations of C(sp3)–H Bonds Using CO2 as the Carbon Source - Pradhan, Suman; Das, Shoubhik (Synlett, 2023)
Carbon dioxide (CO2) is widely known as being a sustainable C1 synthon for the synthesis of various carboxylic acid derivatives, including essential natural and unnatural amino acids. While it is sustainable, the high thermodynamic stability and kinetic inertness of the CO2 molecule is a major drawback to its wider use in organic synthesis. However, the reduction of this inert and highly stable CO2 molecule has been carried out successfully over the past few years using various stoichiometric as well as catalytic approaches. Initially, chemists employed transition-metal/transition-metal-free thermochemical methods for the incorporation of CO2 into organic compounds, however, gradually, the introduction of greener approaches such as visible-light-induced photoredox catalysis and electrocatalysis became revolutionary for the synthesis of carboxylic acids under mild reaction conditions. In this short review, we discuss the recent advances in carboxylation reactions via functionalization of the (sp3)C–H bonds of various organic molecules with CO2 using thermochemical, photochemical and electrochemical methods.1 Introduction2 Transition-Metal/Transition-Metal-Free Thermochemical Carbox ylations of C(sp3)–H Bonds2.1 C(sp3)–H Bond Carboxylation of Carbonyls2.2 Allylic, Benzylic and Alkyl C(sp3)–H Bond Carboxylation3 Photochemical C(sp3)–H Bond Carboxylation3.1 Allylic C(sp3)–H Bond Carboxylation3.2 Benzylic C(sp3)–H Bond Carboxylation4 Electrochemical Carboxylation of C(sp3)–H Bonds5 Conclusion and Outlook
Keywords: carbon dioxide; transition-metal; transition-metal-free; thermochemical strategy; visible-light-induced photocatalysis; electrocatalysis; reductive C–H carboxylations; carboxylic acids